Amyloid Beta Is Internalized via Macropinocytosis, an HSPG- and Lipid Raft-Dependent and Rac1-Mediated Process - Nazere, Keyoumu; Takahashi, Tetsuya; Hara, Naoyuki; Muguruma, Kazuki; Nakamori, Masahiro; Yamazaki, Yu; Morino, Hiroyuki; Maruyama, Hirofumi (Frontiers in Molecular Neuroscience, 2022)
Intracellular amyloid β peptide (Aβ) accumulation has drawn attention in relation to the pathophysiology of Alzheimer’s disease in addition to its extracellular deposition as senile plaque. Cellular uptake of extracellular Aβ is one of the possible mechanisms by which intracellular Aβ deposits form. Given the relevance of Aβ inside cells, it is important to understand the mechanism by which it is taken up by them. In this study, we elucidated that Neuro2A and SH-SY5Y cells internalize specifically oligomerized Aβ in a time- and dose-dependent manner. The depletion of plasma membrane cholesterol with methyl-β-cyclodextrin or treatment with trypsin diminished the internalization of Aβ, suggesting that the Aβ uptake might be both a lipid raft-dependent and heparan sulfate proteoglycan-mediated process. Treatment with a macropinocytosis inhibitor (ethylisopropyl amiloride and wortmannin) also drastically reduced the uptake of oligomer-Aβ (oAβ) by 80.9%. oAβ-treated cells exhibited an increase in Rac1 activity, indicating that macropinocytosis induced by oAβ is regulated by these small GTPases. These findings suggest that macropinocytosis is a major endocytic route through which oAβ42 enters cells.